DETECTION VÍRUS PLRV, PVX E PVY EFFICIENCE ON POTATO TISSUES FROM TUBER END, STOLON END, SPROUTS AND LEAVES BY THE SOROLOGICAL METHOD ENZYME-LINKED IMMUNOSORBENT ASSAY-ELISA - GUEDES, Milton Vasconcelos (Scientia Agraria, 2000)
The vegetative propagation in potatoes (Solanum tuberosum L.) is the cause of varietal degenerescence, once seed tubers from infected mother plants may carry viruses. Therefore, there is a need for constant seedstock renewal, as well as reliable diagnostic techniques. The general objectives of this work were (1) compare the detection efficiency for PLRV, PVV, and PVX under the DAS-ELSA serological test in plant tissues of different origens, tuber end + stolon end, sprouts and Ieaves, alter natural break of dormancy from Baraka, Contenda, and Eivira; (2) verify the reliance of virus detection n dormant, or ealy sprouting tissues n relation to caves, as a matter d time saving to obtain results. Specific objectives were: assess the different viruses incidences in second generation tubers from ware potato fields; compare results from electronic and visual readings in DAS-ELSA tests. Homoscedasticity was tested using the Bartlett test, and mean treatment comparison was done using the Tuckey test, both at 5% probability level. Results were analyzed using MSTATC statistical program, version 2.11. The mean incidence of PVY and PLRV in Baraka, Contenda, and Elvira was greater than the mean incidence of PVX. PVY had the highest incidence in all three cultivars: 14.1%: 10.9, and 2.9 for Baraka, Elvira, and Contenda, respectively. PLRV incidences were, 3.6%, 2.3%, and 0.7% for Elvira, Baraka, and Contenda, respectively. PVX was detected with levels below 0.5% for all 3 cultivars. Contenda presented the lowest incidence for all viruses, as compared to the other cultivars studied. DAS-ELISA could be used to detect PLRV and PVX either in dormant tuber end + stolon end, on in sprouts, or in leaves, after natural break of dormancy, of Baraka, Contenda, and Elvira; the reliance on DAS-ELISA results may change depending on the sample source used; PVY could not be safely detected from tuber end + stolon end samples, for the three studied cultivars. In conclusion, based on the obtained results, it can be said that: detection of viruses in sprouts was more efficient and reliable for all the studied cuitivars, representing a 30 day gain in time to obtain the results.